Geologic Map of the Niobe Planitia Region (I‐2467), Venus - López, Iván (Earth Space Sci, 2020)
We present a 1:10M scale geologic map of the Niobe Planitia region of Venus (0°N–57°N/60°E–180°E). We herein refer to this area as the Niobe Map Area (NMA). Geologic mapping employed NASA Magellan synthetic aperture radar and altimetry data. The NMA geologic map and its companion Aphrodite Map Area (AMA) cover ~25% of Venus' surface, providing an important and unique perspective to study global and regional geologic processes. Both areas display a regional coherence of preserved geologic patterns that record three sequential geologic eras: the ancient era, the Artemis superstructure era, and the youngest fracture zone era. The NMA preserves a limited record of the fracture zone era, contrary to the AMA. However, the NMA hosts a diverse and rich assemblage of material and structures of the ancient era and structures that define the Artemis superstructure era. These two eras likely overlap in time and account for the formation of basement materials and lower plain units. Impact craters formed throughout the NMA recorded history. Approximately 40% of the impact craters show interior flood deposits, indicating that a significant number of NMA impact craters experienced notable geological events after impact crater formation. This and other geologic relations record a geohistory inconsistent with postulated global catastrophic resurfacing. Together, the NMA and the AMA record a rich geologic history of the surface of Venus that provide a framework to formulate new working hypotheses of Venus evolution and to plan future studies of the planet.